Emerging perspectives in big data warehousing - Taniar, David; Rahayu, Johanna Wenny (IGI Global, 2019)
"This book disseminates the latest research findings in the areas of data management and analyzation. It also focuses on the integration between the fields of data warehousing and data mining"--